Upaya Meningkatkan Kematangan Karir Siswa Melalui Bimbingan Kelompok Teknik Role Playing - Ohoiwirin, Yuliana; Permatasari, Devi; Tiarani Soenjanto, Laily (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Career maturity is a stage of individual career development characterized by preparation for the future. The preparations made include seeking career information, understanding oneself in the form of exploring and discovering talents and interests, choosing a future career by using the resources possessed to achieve the appropriate career. The objectives of this study are 1) To determine the level of career maturity of SMA Negeri 10 Malang students before the application of group guidance role playing techniques, 2) To determine the level of career maturity of SMA Negeri 10 Malang students after the application of group guidance role playing techniques, 3) to determine the effectiveness of group guidance role playing techniques effective in increasing the career maturity of SMA Negeri 10 Malang students. The method used in this study uses a type of quantitative research with a research design that is a pre-experiment design with a one group pretest-posttest design model, the sample technique used is simple random sampling. The sample to be examined was 10 students with data analysis techniques using Wilcoxon statistical analysis. Based on the results of the research that has been done, it can be concluded that: 1) The level of career maturity of class XI students of SMA Negeri 10 Malang before being given group guidance on role playing techniques is in the “low” category, 2) Increasing the career maturity of SMA Negeri 10 Malang students after the application of group guidance role playing techniques are in the category of “high and very high”, 3) The results of the Wilcoxon test analysis of the calculation can be concluded that Zhitung is -2.805b and sig. (2-tailed) is 0.005 then HO is rejected so it can be concluded that group guidance role playing techniques are effective for increasing the career maturity of SMA Negeri 10 Malang students. Based on the results of the research conclusions presented above, suggestions can be made for future researchers; this research is expected to be a reference or reference for future researchers who conduct similar research on group guidance with role playing techniques aimed at increasing student career maturity. it is hoped that further research can be improved in the application of group guidance services using role playing techniques to improve student career maturity and a wider subject.